Let There be Variance: Individual Differences in Consecutive Self–Control in A Laboratory Setting and Daily Life. Issue 4 (July 2019) - Wenzel, Mario; Rowland, Zarah; Zahn, Daniela; Kubiak, Thomas
The large body of research used to support ego–depletion effects is currently faced with conceptual and replication issues, leading to doubt over the extent or even existence of the ego–depletion effect. By using within–person designs in a laboratory (Study 1; 187 participants) and an ambulatory assessment study (Study 2; 125 participants), we sought to clarify this ambiguity by investigating whether prominent situational variables (such as motivation and affect) or personality traits can help elucidate when ego depletion can be observed and when not. Although only marginal ego–depletion effects were found in both studies, these effects varied considerably between individuals, indicating that some individuals experience self–control decrements after initial self–control exertion and others not. However, neither motivation nor affect nor personality traits such as trait self–control could consistently explain this variability when models were applied that controlled for variance due to targets and the depletion manipulation (Study 1) or days (Study 2) as well as for multiple testing. We discuss how the operationalization and reliability of our key measures may explain these null effects and demonstrate that alternative metrics may be required to study the consequences of the consecutive exertion of self–control. © 2019 European Association of Personality Psychology